Cardiac magnetic resonance imaging: long term reproducibility of the late enhancement signal in patients with chronic coronary artery disease. Issue 9 (15th August 2005) - Bülow, H; Klein, C; Kuehn, I; Hollweck, R; Nekolla, S G; Schreiber, K; Haas, F; Böhm, J; Schnackenburg, B; Lange, R; Schwaiger, M
Abstract : Objective: To determine long term reproducibility of the late enhancement (LE) signal in contrast enhanced magnetic resonance imaging (MRI) and potential changes of the signal after revascularisation. Methods: 33 patients (29 men, mean (SD) 61 (11) years) with coronary artery disease (CAD) and left ventricular dysfunction (ejection fraction 30 (7)%) underwent two contrast enhanced MRI procedures within 9 (3) months. Fifteen patients (group A: 14 men, 59 (12) years) had no interventions between the two studies. Eighteen patients underwent revascularisation after MRI 1 (group B: 15 men, 62 (9) years). Changes in the LE signal between the first and second MRIs were investigated in both groups as well as intraobserver and interobserver variabilities for delineation of the signal. Results: The LE signal was highly reproducible in groups A and B for segmental analysis (concordance 86% v 82%, respectively; κ  =  0.70 v 0.67) and summed scores (group A: r  =  0.97, p < 0.001; group B: r  =  0.93, p < 0.001). The LE signal was quantified as 27 (27) cm 3 in group A versus 30 (16) cm 3 in group B in the first MRI and 26 (25) cm 3 versus 30 (15) cm 3, respectively, for the second MRI (both not significant). Moreover, low intraobserver and interobserver variabilities were observed in segmental analysis (κ  =  0.86 and 0.74, respectively, for group A, and κ  =  0.87 and 0.82, respectively, for group B). Conclusion: In patients with chronic CAD, the LE signal in contrast enhanced MRI is very stable over an extended time period. These results further characterise contrast enhanced MRI as a useful tool for myocardial viability assessment. Low intraobserver and interobserver variabilities promise robustness of the method for clinical application.